Dialectic of Islam and West Ethics in the Business World - Johan Arifin (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2008)
The appearance of the modernity has resulted in many revolutions on human lives. Since the intervention of highly modern devices in communication, for instance, we find multitude of ways how humans express their will to get in touch with one another in extremely unimaginable manners long time ago. This has much benefited people for they are getting easier to do and get everything in this modern world. Nonetheless, not only does this results in merely positive impacts, but there we also find how modernity has overshadowed many worldly traditional norms and, in some degrees, has made them blurred in daily relation. Basically, those ’traditi¬onal’ norms function as a code of conduct for human to mirror their deed so that the broke of this worldly life can be avoided. In this sense, it will be interesting when we relate The West and Islam in announcing the salience of a norm and its values in daily modern lives. This essay wants to look at briefly how Islam and the West appeal humans to internalize ethical norms in daily interaction, especially in the world of business.Keywords: Ethics, Business, Islam, West.